Pomiędzy policentryzmem a autocentryzmem : kryzys Fiata Auto na przełomie XX i XXI wieku - Figuła, Jerzy (Wydawnictwo Uniwersytetu Wrocławskiego, 2013)
The paper analyses strategic decisions employed by Fiat Company at the turn of the centuries. Faced with stagnation in the automotive industry and low profitability of passenger car production at that time, the management considered the possibility of departing from main production activities and seeking profit in related business and service sectors. The paper studies the effects and potential consequences of the strategic alliance between Fiat and GM. The internationalization of vehicle production and sales, coupled with Fiat’s entry on the markets of South America and Asia, seem to have improved the company chances for sustainable growth. The strategic alliance with GM has also improved the potential for implementing a wide range of R&D projects at hand
Keywords: przemysł samochodowy; strategia przedsiębiorstwa; Fiat Auto